DAILY ACTIVITY OF EARLESS MONITOR Lanthanotus borneensis STEINDACHNER, 1878 IN A CAPTIVE ENVIRONMENT - Amat Ribut; Evy Arida; Riyandi (BRIN Publishing (Penerbit BRIN), 2024)
The Earless monitor (Lanthanotus borneensis Steindachner, 1878) is a rare and endemic species of lizard to the island of Borneo. Individuals of this species were often culled to supply the international pet market and have been kept in captivities, also in the northern temperate areas. This study aimed to describe the daily activities of L. borneensis at the reptile house of Museum Zoologicum Bogoriense (MZB), a live animal research facility of the former Indonesian Institute of Sciences (LIPI) - now merged into BRIN. Focal animal sampling was used to observe L. borneensis behavior for two hours per individual in the morning (09:00–11:00) and afternoon (15:15–17:15) with the assistance of surveillance cameras (CCTV), resulting in a total observation time of 16 hours per individual per two months. The observations of 10 individuals of L. borneensis showed that they were more inactive in the morning, with a tendency to be more active and feeding in the afternoon. During inactivity, lizards remained motionless in the bamboo; when active, they were moving in water and foraging.